Exploring Group Behavior in a Power-to-Take Video Experiment - Ronald Bosman; Heike Hennig-Schmidt; Frans vanWinden (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
This paper experimentally explores group decision-making in a two-player power-to-take game. Discussions preceding group decisions are video taped and analyzed. Each subject first earns an income in an individual effort task preceding the game. The game consists of two stages. First, one group can claim any part of the income of the other group (take rate). Then, the latter group can respond by destroying own income. The results show that (1) although group behavior is in line with individual behavior, group behavior depends crucially on the decision rules that subject use to arrive at their group decision; (2) groups ignore the decision rule of their `opponents' and typically view other groups as if they were single agents; (3) perceptions of fairness are prone to the so-called self-serving bias. (4) expectations are often not consistent with actual outcomes.
Keywords: A12; C72; C91; C92; 330; groups; decision rule; fairness; experiment; video